Serological Survey of the Infection of Parainfluenzavirus Type 3 in Cattle in Malatya - Özdarendeli, Aykut; Kandil, Mehmet (My University, 2001)
Cattle serum samples were examined for antibodies to parainflue nza type 3 (PI-3) virus using the hemaglutination-inhibition (HI) test. These sera were taken in autumn 1994 and spring 1995 from clinically healthy cattle in Malatya. Antibodies to PI-3 virus were detected in 897 out of 1000 cattle sera 89.7%. Reciprocal antibody titres to PI-3 virus in cattle ranged from 1:16 to 1:1024. It was determined that the proportion of seropositive sera in the cattle in the spring was higher than in the autumn.
Malatya'da Si?irlarda Parainfluenzavirus Tip-3 Enfeksiyonu Üzerinde Serolojik Araştirma
Keywords: Cattle; HI-Antibodies; Parainfluenzavirus type 3